Subthreshold Operation of Organic Electrochemical Transistors for Biosignal Amplification. Issue 8 (4th July 2018) - Venkatraman, Vishak; Friedlein, Jacob T.; Giovannitti, Alexander; Maria, Iuliana P.; McCulloch, Iain; McLeod, Robert R.; Rivnay, Jonathan
Abstract: With a host of new materials being investigated as active layers in organic electrochemical transistors (OECTs), several advantageous characteristics can be utilized to improve transduction and circuit level performance for biosensing applications. Here, the subthreshold region of operation of one recently reported high performing OECT material, poly(2‐(3, 3′‐bis(2‐(2‐(2‐methoxyethoxy)ethoxy)ethoxy)‐[2, 2′‐bithiophen]‐5‐yl)thieno[3, 2‐ b ]thiophene), p(g2T‐TT) is investigated. The material's high subthreshold slope (SS) is exploited for high voltage gain and low power consumption. An ≈5× improvement in voltage gain ( A V ) for devices engineered for equal output current and 370× lower power consumption in the subthreshold region, in comparison to operation in the higher transconductance ( g m ), superthreshold region usually reported in the literature, are reported. Electrophysiological sensing is demonstrated using the subthreshold regime of p(g2T‐TT) devices and it is suggested that operation in this regime enables low power, enhanced sensing for a broad range of bioelectronic applications. Finally, the accessibility of the subthreshold regime of p(g2T‐TT) is evaluated in comparison with the prototypical poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), and the role of material design in achieving favorable properties for subthreshold operation is discussed. Abstract : Organic electrochemical transistors can achieve subthreshold slopes of 60 mV dec −1 . Operation in this regime is shown to provide favorable gain and low power characteristics for sensing circuits. Subthreshold voltage amplification is demonstrated for recording electroencephalography signals.